Easy Steps To Search And Use Hadith For The General Public - Muhammad Amin (AQWAL Journal of Qur'an and Hadis Studies, 2022)
This article examines the challenges of academics in dealing with the general public to describe concrete steps in their need for the hadith of the Prophet. Society is not only faced with the statuses of hadith, but also issues of understanding, search, books and so on. Therefore, the main purpose of this paper is to try to see a simple design in studying and practicing hadith so as to make it easier for the general public to interact with the hadith. Answering this question, this study uses a literature review with a discourse analysis approach. This study shows that an easy and practical step for the general public is to search for hadith through the application or web of a takhrīj service provider quickly and friendly to use. There needs to be a gesture of realization that the hadith narrated in general is not singular; both the pronunciation, the narration and the matan. The move can be implemented with i'tibār al-Sanad. Society also needs to emphasize the existence of a benchmark of hadith status that has been set by the muḥaddiṡīn; Both from the status of sanad and matan. The two points are inseparable because they are an integral part of the study of the Prophet's hadith.